2022
DOI: 10.21203/rs.3.rs-1854496/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microencapsulation of rosemary Rosmarinus officinalis essential oil by Chitosan - gum Arabic and its application for the control of two secondary pests of stored cereals

Abstract: Encapsulation of Rosmarinus officinalis essential oil (EO) on chitosan and gum Arabic matrix were prepared at different ratios with various concentrations of essential oil. The capsules were characterized by their encapsulation efficacy (EE%) and loading capacity (LC%). The cumulative release profiles were evaluated by UV/Vis spectroscopy. The chemical compounds for free and encapsulated essential oil were determined by GC-MS technique and the insecticidal toxicity against Tribolium castaneum and Oryzeaphilus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…In fact, in Soltani and co-authors [42], fumigation tests with nanocapsules of chitosan loaded with Rosmarinus officinalis EO showed an extension of mortality over time of T. castaneum (20% mortality after 60 days compared to the pure EO after the same time, at 2.1%). These results were confirmed by Soltani and co-authors [43,44], who reported that the rosemary oil nanoencapsulated by chitosan exhibited 82% and 50.7% mortality after 60 days against Oryzaephilus surinamensis (Linnaeus, 1758) (Coleoptera, Silvanidae) and Carpophilus hemipterus (Linnaeus, 1758) (Coleoptera, Nitidulidae) compared to the neat EO (62% and 19% mortality, respectively). Following these results, the EO nanoencapsulation in chitosan was more effective than the neat EO even over time.…”
Section: Figuresupporting
confidence: 70%
“…In fact, in Soltani and co-authors [42], fumigation tests with nanocapsules of chitosan loaded with Rosmarinus officinalis EO showed an extension of mortality over time of T. castaneum (20% mortality after 60 days compared to the pure EO after the same time, at 2.1%). These results were confirmed by Soltani and co-authors [43,44], who reported that the rosemary oil nanoencapsulated by chitosan exhibited 82% and 50.7% mortality after 60 days against Oryzaephilus surinamensis (Linnaeus, 1758) (Coleoptera, Silvanidae) and Carpophilus hemipterus (Linnaeus, 1758) (Coleoptera, Nitidulidae) compared to the neat EO (62% and 19% mortality, respectively). Following these results, the EO nanoencapsulation in chitosan was more effective than the neat EO even over time.…”
Section: Figuresupporting
confidence: 70%